How to Enhance the Effectiveness of the Learning Process During Distance Learning. Psychologist Recommendations - Kapanadze, Tamar (Journal of Legal Studies, 2021)
Effective management of the learning/teaching process in distance learning is one of the major challenges facing education, especially now in the Covid-19 pandemic. The list of problems mainly combines social and interactive aspects. This article provides tips to help the student increase motivation, overcome feelings of social isolation, find alternative ways of communicating and, develop communication skills. The aim of the research is to identify the pros and cons of online learning, thus finding out how to improve the effectiveness of the learning process during distance learning. The research was obtained through a focus group, the research was conducted in Tbilisi public schools, students, teachers and parents participated in the focus groups. After analyzing the data, it was found that participants positively see such a form of teaching, which in turn would have a positive impact on students' academic performance, but they also talk about small negative aspects.